Analisis Peranan Penilaian Persediaan Barang Dagang terhadap Laba pada PT. Fajar Lestari Abadi Makassar - Rostiaty Yunus (STIM LASHARAN JAYA MAKASSAR, 2017)
The research was conducted at PT. Fajar Abadi Lestari Makassar is located at street Kima 4 Kav M / 2 Power Industrial Area, Makassar. Penelitian Biringkanaya was conducted for about 2 bulanyaitu began June-Juli.Metode analysis used in this research is quantitative descriptive method with which this technique can be interpreted as the inventory valuation method to compare with some of the methods can then be known which method is most appropriate to use in certain situations and conditions and their effect on profit improvement. Based on the results of research and discussion conducted by the author, the authors put forward some conclusions are as follows: Rating Merchandise Inventory is one of the factors that contribute to profits for the assessment of inventory appropriately, then the company can determine the value of the merchandise inventory as well as the magnitude cost of goods sold which will be presented in the financial statements, Assessment Inventory for the period from January to April has been implemented effectively by PT. Fajar Abadi Lestari Makassar, this can be seen from an increase in profits earned by the company when using the FIFO method during January. In assessing the merchandise inventory using the FIFO method the total profit earned during January to April is higher, it is due to an increase in prices. FIFO method will produce the lowest cost of sales, gross profit and net income and highest-highest ending inventory.